Method Modification of the Thermo Scientific SureTect Listeria monocytogenes Assay for Raw Meat, Dairy, Produce, and Seafood. (27th November 2019) - Cloke, Jonathan; Evans, Katharine; Crabtree, David; Hughes, Annette; Simpson, Helen; Leon-Velarde, Carlos; Larson, Nathan; Dave, Keron; Holopainen, Jani; Wickstrand, Nina; Kauppinen, Mikko
Abstract: The Thermo Scientific™ SureTect™ Listeria monocytogenes assay is a real-time PCR assay for the detection of Listeria monocytogenes in food and environmental samples, which was certified during 2013 by the AOAC Research Institute (RI) as Performance Tested Method SM (PTM) 061302 for a representative range of key food matrixes and production surfaces. This report details the method modification study, which was conducted during 2014, using the AOAC-RI PTM program to extend the validated matrix claims of the assay in comparison to the reference method detailed in International Organization for Standardization 11290-1:1996, including Amendment 1:2004, to gain certification for raw ground turkey, raw ground pork, pasteurized 2% milk, raw pork sausages, raw cod, pasteurized brie cheese, cooked sliced ham, and bagged lettuce. All matrixes were tested by Thermo Fisher Scientific, Microbiology Division, Basingstoke, UK. In addition, brie cheese, bagged lettuce, and raw cod were analyzed independently by the University of Guelph, Canada, during the AOAC-RI controlled independent laboratory study. Using probability of detection (POD) statistical analysis, a significant difference was demonstrated between the candidate and reference methods for the high spiking level with raw ground pork and brie cheese. For all other matrixes and the low spiked levels for raw ground pork and brie cheese, no significant difference by POD was seen between the two methods during the study.